Opportunities for education and learning in primary care genomics. Issue 2 (February 2021) - Bishop, Michelle; Hayward, Judith; Rafi, Imran
The continued evolution of the NHS Genomic Medicine Service, alongside improved accessibility to genomic testing through other routes, will increase consultations regarding genomics issues within primary care. GP trainees identify 'genetics' as a learning gap in their training, with anecdotal evidence suggesting that completion of this section in the curriculum is 'challenging'. To support trainees and trainers in meeting this aspect of GP training, this article outlines relevant educational theory, initiatives and resources in genomics from a primary care perspective. This information will equip the learner with approaches and tools to promote confidence in learning and managing issues involving genomic medicine in practice.